PENERAPAN STRATEGI JOYFUL LEARNING DALAM HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS V SDN 5 KARANG ANYAR - Atika Nur Hidayati; Vera Veriani; Rohini (STIT Darul Fattah Bandar Lampung, 2023)
This study aims to determine and analyze the increase in problem-solving abilities in mathematics learning outcomes of fifth grade students at SD Negeri 5 Karang Anyar South Lampung through a joyful learning strategy. The research problem is the low interest and interest of students in mathematics so that it affects the low results of learning mathematics. The research subjects were students in class V-A Odd Semester at SD Negeri 5 Karang Anyar, South Lampung, which consisted of 24 students, while the objects in the study were the results of learning mathematics. The implementation method uses two stages, namely: the preparation stage and the implementation stage. The results of the study show that the use of joyful learning strategies can improve the mathematics learning outcomes of fifth grade students at SDN 5 Karang Anyar Jati Agung South Lampung in the 2022 academic year